trebuie derivat
![( \frac{ {e}^{2x} - 1}{ {e}^{x} } ) ( \frac{ {e}^{2x} - 1}{ {e}^{x} } )](https://tex.z-dn.net/?f=%28+%5Cfrac%7B+%7Be%7D%5E%7B2x%7D+-+1%7D%7B+%7Be%7D%5E%7Bx%7D+%7D+%29)
vă rog frumos
Răspunsuri la întrebare
Răspuns de
1
Formula (f/g)` = (f`*g - f*g`)/g²
[(e²ˣ -1)/eˣ]` =
[(e²ˣ)`*(-1) - e²ˣ**(-1)`] / (eˣ)² =
[e²ˣ*(2x)` *(-1) - e²ˣ *0] / e²ˣ =
-2e²ˣ /e²ˣ = -2
lee851661:
Mulțumesc
Alte întrebări interesante
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
9 ani în urmă
Geografie,
9 ani în urmă
Limba română,
9 ani în urmă